Social Media Effects on Muslim Domestic Conflicts: Family Conflict Theory and Digital Fiqh Perspective - Muthmainnah; Supriati Hardi Rahayu (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
Background Social media has become an integral part of modern life, including within Muslim families. Although it facilitates communication, excessive use may trigger domestic conflict and marital instability. Objective: This study examines the influence of social media use on domestic conflict among Muslim families, focusing on usage intensity, online activities, digital fiqh knowledge, and marriage duration. Method: This study employed a quantitative explanatory approach using a cross-sectional survey of 300 Muslim couples who actively use social media. Data were collected using a 5-point Likert-scale questionnaire and analyzed in SPSS, including regression and moderation analyses. Results: Social media intensity significantly affects domestic conflict (β = 0.415; p < 0.001), with interactions with non-mahrams showing the strongest effect (β = 0.462; p < 0.001). Digital fiqh knowledge mitigates the negative influence of social media (β = −0.173; p < 0.05), whereas newly married couples experience higher levels of conflict. Conclusion: Social media contributes to domestic conflict, whereas digital fiqh literacy mitigates its negative effects. This study strengthens the integration of Family Conflict Theory and Islamic law by positioning digital fiqh literacy as a religio-normative mechanism for regulating online behavior and maintaining family harmony in the digital era.